Pathotype determination of sorghum anthracnose (Colletotrichum sublineola) isolates from Ethiopia using sorghum differentials - Mekonen, Moges; Tesfaye, Kassahun; Mengiste, Tesfaye; Chala, Alemayehu; Nida, Habte; Mekonnen, Tilahun; Abreha, Kibrom B.; Geleta, Mulatu (Frontiers in Microbiology, 2024)
Sorghum anthracnose caused by Colletotrichum sublineola, is the most destructive disease of sorghum, which causing up to 80% grain yield loss in susceptible varieties. The use of resistance varieties is an effective, durable, and eco-friendly strategy for anthracnose control. Knowledge of the phenotypic and genetic variation in C. sublineola is vital for designing appropriate anthracnose management strategies. The present study examined the morphology and virulence of 25 C. sublineola isolates recovered from various sorghum producing regions of Ethiopia against 18 known sorghum anthracnose differentials and six Ethiopian sorghum landraces and a variety Bonsa. Analysis of variance (ANOVA) revealed significant differences among sorghum genotypes, C. sublineola isolates and their interactions. There was a significant difference between the isolates in virulence, with each isolate exhibiting virulence in 8-72% of the sorghum genotypes tested. Among the 25 tested isolates, the top four most virulent isolates were from Pawe, suggesting that this area is suitable for pathogen diversity studies and host plant resistance screening. The sorghum genotypes IS_18760, Brandes and Bonsa showed resistance to all tested isolates. Consequently, they may provide potential sources of resistance genes for sorghum breeding programs to develop cultivars resistant to different C. sublineola pathotypes. However, the resistant check SC748-5 was susceptible to isolates NK73_F37 while another resistant check SC112-14 was susceptible to isolates PW123_F47 and PW122_F47. Cluster analysis grouped 22 isolates into seven clusters based on their morphological characters whereas 24 pathotypes were identified among 25 isolates that were tested on 25 sorghum genotypes. Hence, this study revealed high variation in C. sublineola in Ethiopia suggesting the need for broad spectrum resistance to control the disease. Sorghum genotypes resistant to various C. sublineola isolates were identified in this study, which can be used in sorghum breeding programs aiming to develop resistant cultivars to anthracnose. Highly virulent C. sublineola isolates were also identified which could be used in sorghum germplasm resistance screening. The report is the first to show the existence of C. sublineola pathotypes in Ethiopia.